Penegakan Hukum terhadap Pertambangan Batu Bara Ilegal di Wilayah Samarinda Kalimantan Timur - Darmin Sumanggi (PT Elaborium Elevasi Indonesia, 2023)
Mining management in Indonesia which is currently given the authority to be delegated to each region that has the potential for natural resources, as stated in CHAPTER VI of the 1945 Constitution of the Republic of Indonesia after the amendment of Regional Government. Article 18 paragraph (5) states that